Hardware asist verification - Bondarenko, I.; Karnaushenko, V.; Shcherban, I. (ХНУРЕ, 2025)
The rapid development of semiconductor technology is driven by four complex elements: software, hardware, interface, and architecture. As modern chips integrate billions of transistors, support heterogeneous computing, and perform increasingly software-defined workloads, ensuring their functionality has never been more challenging. Modern systems use complex software stacks, requiring early software validation along with hardware verification. HAV platforms allow for pre-silicon software creation through FPGA-based emulation and prototyping.
Keywords: high-performance computing; SoC; FPGA